Active surveillance for carbapenemase-producing Klebsiella pneumoniae and correlation with infection in subjects attending an Italian tertiary-care hospital: a 7-year retrospective study - Adriana Calderaro; Mirko Buttrini; Monica Martinelli; Sara Montecchini; Silvia Covan; Alberto Ruggeri; Isabella Rodighiero; Alan Di Maio; Mariapia Galullo; Sandra Larini; Maria Cristina Arcangeletti; Carlo Chezzi; et al. (BMJ Open)
Objectives The distribution of carbapenemase-producing Klebsiella pneumoniae (CPKP) phenotypes and genotypes in samples collected during 2011–2018 was evaluated. The association between patients with CPKP-positive rectal swab and those with CPKP infection, as well as the overall analysis of CPKP-infected patients, was performed.Setting The study was performed in a tertiary-care hospital located in Northern Italy.Participants Two groups were considered: 22 939 ‘at-risk’ patients submitted to active surveillance for CPKP detection in rectal swabs/stools and 1094 CPKP-infected patients in which CPKP was detected in samples other than rectal swabs.Results CPKP-positive rectal swabs were detected in 5% (1150/22 939). A CPKP infection was revealed in 3.1% (719/22 939) of patients: 582 with CPKP-positive rectal swab (50.6% of the 1150 CPKP-positive rectal swabs) and 137 with CPKP-negative rectal swab. The 49.4% (568/1150) of the patients with CPKP-positive rectal swab were carriers. The overall frequency of CPKP-positive patients (carriers and infected) was almost constant from 2012 to 2016 (excluding the 2015 peak) and then increased in 2017–2018. blaKPC was predominant followed by blaVIM. No difference was observed in the frequency of CPKP-positive rectal swab patients among the different material groups. Among the targeted carbapenemase genes, blaVIM was more significantly detected from urine than from other samples.Conclusions The high prevalence of carriers without evidence of infection, representing a potential reservoir of CPKP, suggests to maintain the guard about this problem, emphasising the importance of active surveillance for timely detection and separation of carriers, activation of contact precautions and antibiotic treatment guidance on suspicion of infection.